2010
DOI: 10.1007/s11033-010-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids and lipoproteins in children and young adults with major β-thalassemia from western Iran: influence of genotype

Abstract: To determine the plasma lipid and lipoprotein profiles and their possible association with the type of β-thalassemia mutation we studied 103 major β-thalassemia patients including 71 children and 32 young adults compared to 102 healthy subjects consisted of 90 children and 12 young healthy adults. The plasma lipid and lipoprotein levels were measured by conventional methods. Considering all of the patients the levels of total cholesterol (TC), LDL-cholesterol (LDL-C), and HDL-cholesterol (HDL-C) were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A recent report from Azizi et al18 which enrolled healthy children and adolescents from Iran has suggested that 16% of males and females at our patients' ages had high total cholesterol. According to the previous studies, it is known that patients with beta-thalassemia major have lower total cholesterol levels compared with healthy individuals of the same age 19. Based on the previous findings in thalassemic patients, we also observed low mean LDL-C levels in our subjects.…”
Section: Discussionsupporting
confidence: 79%
“…A recent report from Azizi et al18 which enrolled healthy children and adolescents from Iran has suggested that 16% of males and females at our patients' ages had high total cholesterol. According to the previous studies, it is known that patients with beta-thalassemia major have lower total cholesterol levels compared with healthy individuals of the same age 19. Based on the previous findings in thalassemic patients, we also observed low mean LDL-C levels in our subjects.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, plasma vitamin C may be depleted due to iron overload and formation of excessive radicals (H 2 O 2 ). and lower HDL-C, LDL-C was found in the patients with β-thalassemia major (11). Several mechanisms, including accelerated erythropoiesis, cholesterol consumption, liver dysfunction, iron overload, and oxidative stress, have been described for alterations of lipid and lipoprotein levels in β-thalassemia patients (12).…”
Section: Discussionmentioning
confidence: 97%
“…Iron overload in moderate and severe patients is still the major reason for long‐term, life‐threatening complications even though such patients have undergone intense iron‐chelating treatment. More severe liver damage with higher ALT, GGT, TG, and lower HDL‐C, LDL‐C was found in the patients with β‐thalassemia major . Several mechanisms, including accelerated erythropoiesis, cholesterol consumption, liver dysfunction, iron overload, and oxidative stress, have been described for alterations of lipid and lipoprotein levels in β‐thalassemia patients .…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results were reported for the antioxidant state in b-thal patients, as measured by the levels of catalase (CAT) activity and reduced glutathione (GSH) (9,10). Lipid profile and redox status studies in splenectomized patients are very limited (11,12) and potential correlation with plasma lipids profile or with clinical data is not well known. The aim of this study was to investigate in b-thal patients and control subjects, the levels of TG, TC, HDL-C, LDL-C, the LDL/ HDL LDL/TG and TC/HDL ratios and the oxidative markers such as CAT activity, MDA and GSH levels.…”
Section: Introductionmentioning
confidence: 99%